IDENTIFIKASI INDUSTRI KREATIF UNTUK MENDUKUNG DESA BANYUURIP DI KABUPATEN GRESIK SEBAGAI DESA WISATA BUNGA - Aidil Primasetya Armin (Jurnal Pendidikan Tata Niaga (JPTN), 2022)
This study aims to identify the tourism village supporting industry in Banyuurip Village, Kedamean District, Gresik Regency, determine the existing condition of the tourism village support industry in Banyuurip Village, Kedamean District, Gresik Regency, and provide recommendations for the development of supporting industries in Banyuurip Village as a tourist village. The village that has the potential to be improved as a tourist village is Banyuurip Village which is famous for its flower market. Miru Hamlet and Pendem Hamlet located in Banyuurip Village have thousands of types of ornamental plant varieties that can be used as export commodities. The concept of the creative economy is expected to be able to build a village economy where the products produced are highly competitive. The existing creative industries will be seen for their existing conditions, whether there are any that need to be developed and maintained. This research is important considering thatBanyuurip Village has great potential to become a flower tourism destination in Gresik Regency. The research method used is descriptive statistical method and qualitative method. The result of this research is the realization of the Flower Tourism Village. The result of this research is the realization of the Flower Tourism Village. The results show that the type of supporting industry that has the potential to be developed is food and beverage, the majority of which are spread across four hamlets in Banyuurip Village along Bunga Tourism.